Negligible effects of ß-Hydroxy-ß-Methylbutyrate free acid and calcium salt on strength and hypertrophic responses to resistance training: A randomized, placebo-controlled study - Tritto, A. C.; Bueno, S.; Rodrigues, R. M. P.; Gualano, B.; Roschel, H.; Artioli, G. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
This study evaluated the effects of ß-hydroxy-ß-methylbutyrate free acid (HMB-FA) and calcium salt (HMB-Ca) on strength, hypertrophy, and markers of muscle damage. In this randomized, double-blind, placebo-controlled study, 44 resistance-trained men (age: 26 ± 4 years; body mass: 84.9 ± 12.0 kg) consuming =1.7 g·kg-1·day-1 of protein received HMB-FA (3 g/day; n = 14), HMB-Ca (3 g/day; n = 15), or placebo (PL; cornstarch, 3 g/day; n = 15) for 12 weeks, while performing a periodized resistance training program. Before and after intervention, lean body mass (measured with dual X-ray absorptiometry), maximal dynamic strength (one-repetition maximum), knee extension maximal isometric strength (maximal voluntary isometric contraction [MVIC]), cross-sectional area (measured with ultrasound), and muscle soreness were assessed. MVIC was also measured 48 hr after the first and the last training sessions. All groups increased lean body mass (main time effect: p < .0001; HMB-FA: 1.8 ± 1.8 kg; HMB-Ca: 0.8 ± 1.4 kg; PL: 0.9 ± 1.4 kg), cross-sectional area (main time effect: p < .0001; HMB-FA: 6.6 ± 3.8%; HMB-Ca: 4.7 ± 4.4%; PL: 6.9 ± 3.8%), one-repetition maximum bench press (main time effect: p < .0001; HMB-FA: 14.8 ± 8.4 kg; HMB-Ca: 11.8 ± 7.4 kg; PL: 11.2 ± 6.6 kg), MVIC (main time effect: p < .0001; HMB-FA: 34.4 ± 39.3%; HMB-Ca: 32.3 ± 27.4%; PL: 17.7 ± 20.9%) after the intervention, but no differences between groups were shown. HMB-FA group showed greater leg press strength after the intervention than HMB-Ca and PL groups (Group × Time interaction: p < .05; HMB-FA: 47.7 ± 31.2 kg; HMB-Ca: 43.8 ± 31.7 kg; PL: 30.2 ± 20.9 kg). MVIC measured 48 hr after the first and the last sessions showed no attenuation of force decline with supplementation. Muscle soreness following the first and last sessions was not different between groups. The authors concluded that neither HMB-Ca nor HMB-FA improved hypertrophy or reduced muscle damage in resistance-trained men undergoing resistance training ingesting optimal amounts of protein. HMB-FA but not HMB-Ca resulted in a statistically significant yet minor improvement on leg press one-repetition maximum.